2021
DOI: 10.32604/fdmp.2021.016507
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Changing Characteristics of Flow-Induced Noise in a Centrifugal Pump

Abstract: Centrifugal pumps are widely used in engineering for a variety of applications. A known drawback of these devices is the high-level noise generated during operations, which can affect their stability and adversely influence the entire working environment. By combining the Powell vortex sound theory, numerical simulations and experimental measurements, this research explores the trends of variation and the corresponding underlying mechanisms for the flow-induced noise at various locations and under different op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Through theoretical analysis of the dynamic characteristics of the fluid particles in the impeller, the effects of the rotational centrifugal force, Coriolis force, and curved centrifugal force on the movement characteristics of the fluid particles in the impeller were identified, and ways for impeller hydraulic optimization were proposed. In literature [9], by combining the Powell vortex sound theory, numerical simulations and experimental measurements, this research explores the trends of variation and the corresponding underlying mechanisms for the flow-induced noise at various locations and under different operating conditions. It is shown that the total sound source intensity (TSSI) and total sound pressure level (TSPL) in the impeller, in the region between the inlet to the outlet and along the circumferential extension of the volute, are much higher than those at pump inlet and outlet.…”
Section: Introductionmentioning
confidence: 99%
“…Through theoretical analysis of the dynamic characteristics of the fluid particles in the impeller, the effects of the rotational centrifugal force, Coriolis force, and curved centrifugal force on the movement characteristics of the fluid particles in the impeller were identified, and ways for impeller hydraulic optimization were proposed. In literature [9], by combining the Powell vortex sound theory, numerical simulations and experimental measurements, this research explores the trends of variation and the corresponding underlying mechanisms for the flow-induced noise at various locations and under different operating conditions. It is shown that the total sound source intensity (TSSI) and total sound pressure level (TSPL) in the impeller, in the region between the inlet to the outlet and along the circumferential extension of the volute, are much higher than those at pump inlet and outlet.…”
Section: Introductionmentioning
confidence: 99%
“…Si et al (2019) summarized the recent developments of the flow-induced noises in a centrifugal pump; especially, the different numerical and experimental methods that had been used to analyze the internal flow properties and its effect on the generation of flow-induced noise. Li et al (2021) explored the trends of variation and the corresponding underlying mechanisms for flow-induced noise at various locations and under different operating conditions. Jiang et al (2007) used multi-stage centrifugal pump and showed that the generation of noise could be best calculated by the fluid-structure weakly coupled simulations.…”
mentioning
confidence: 99%